Concatenative Sound Synthesis as a Technomorphic Model in Computer-Aided Composition - Guatimosim, Júlio; Padovani, José Henrique; Guatimosim, Carlos (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19431, 2021)
The text presents a process aimed at computer-aided composition for percussion instruments based on Concatenative Sound Synthesis (CSS). After the introduction, we address the concept of ”technomorphism” and the influence of electroacoustic techniques in instrumental composition. The third section covers processes of instrumental sound synthesis and its development in the context of Computer-Aided Composition (CAC) and Computer-Aided Music Orchestration (CAMO). Then, we describe the general principles of Concatenative Sound Synthesis (CSS). The fifth section covers our adaptation of CSS as a technomorphic model for Computer-Aided Composition/Orchestration, employing a corpus of percussion sounds/instruments. In the final section, we discuss future developments and the mains characteristics of our implementation and strategy.